JURIDICAL REVIEW OF THE WINNING OF THE EMPTY BOXES IN REGIONAL HEAD ELECTIONS - Muhammad Rizqi Fadhlillah; Yusmedi Yusuf; Ratna Indayatun; Hasan Hamid Safri (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Elections for Regional Heads or commonly known as “Pilkada” are carried out directly by residents of the local administrative area who meet the requirements. The election of regional heads is carried out in a package together with the deputy regional heads. The regional heads and deputy regional heads in question include the governor and deputy governor for the province, the mayor and the deputy mayor for the city, and the regent and deputy regent for the district. Regarding the elections, By law, winning the empty box is allowed based on Article 54 D (2) of Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning Election of Governors, Regents , and the Mayor becomes Law. However, the next question is that the official appointed by the government based on the winner of the empty box represents legal interests. This has not been regulated by the government, so it is necessary to revise the latest Law to find out about it. Keywords: Election, Regional Head, Empty Box